PENGALAMAN HIDUP PASIEN PASKA STROKE DI BANDUNG (The Life Experiences of Post-Stroke Patients In Bandung) - Setiawan, Iriani Dewi; Trisyani, Yanny; Lumbantobing, Valentina Belinda Marlianti (Journal Nursing Care and Biomolecular, 2018)
Introduction: Stroke is the second leading cause of death in the world and the most common disability-causing disease. Stroke causes the physical changes of paralysis, social changes of communication problems, cognitive impairment and psychological effects of difficulty in understanding, forgetfulness, and depression. The impact of post-stroke patients is very complex and comprehensive in terms of physical, psychological, and social change. Health workers, especially nurses need to provide nursing care in post-stroke patients comprehensively. The purpose of this study was to explore the life experiences of post-stroke patients. Method:The research method used in this study was phenomenology. The subjects in this study were post-stroke patients with the number of informants of 6 post-stroke patients obtained through purposive sampling technique. The data collection was conducted through in-depth interviews with the help of recording devices conducted in March-April 2017. Result and analysis: The data were analyzed using Collaizi. Â The results of the study showed that there were five themes related to the life experiences of post-stroke patients, namely: helplessness, sadness, anger, shame of life uncertainty, and decrease of social contact and hope to be healed. In conclusion, the results showed that post-stroke patients had physical and functional disorders causing psychological and social responses that affected the life experience. Discussion: Based on the results of this study, it is necessary to provide the peer support of post-stroke patients and appropriate information by health workers, family and the environment to help patients undergo the process of treatment and recovery.Â